Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Pada Home Industry “Donat Paha Ayam” - Ahmad Faisol Amir; Yustina Chrismardani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
Determining a good strategy in facing competition in the market is one of the keys to the company's success in marketing its goods and services. One of the business world where the level of competition is currently increasing from year to year is the production of home industries in the form of food, one of which is the home industry of chicken thigh donuts. a good marketing strategy in order to increase the volume of sales in each of its products so as to get the maximum profit or profit for the sustainability of the business to improve and develop. The type of research used in this research is qualitative research. The marketing strategy applied by the Chicken Thigh Donut Home Industry to increase its sales volume and the ability to compete for its products has been going well by paying attention to the quality of quality products and setting the selling price of the product that is not too high, but the distribution and promotion channels are carried out in a simple manner that needs to be developed again so that can escalate into a bigger business. Efforts that must be made by the Chicken Thigh Donut Home Industry so that its business activities run well and optimally are by establishing the right marketing strategy and having more competitive advantages that can increase sales volume and product competitiveness.